Investigations on response time of magnetorheological elastomer under compression mode. (20th April 2018) - Zhu, Mi; Yu, Miao; Qi, Song; Fu, Jie
Abstract: For efficient fast control of vibration system with magnetorheological elastomer (MRE)-based smart device, the response time of MRE material is the key parameter which directly affects the control performance of the vibration system. For a step coil current excitation, this paper proposed a Maxwell behavior model with time constant λ to describe the normal force response of MRE, and the response time of MRE was extracted through the separation of coil response time. Besides, the transient responses of MRE under compression mode were experimentally investigated, and the effects of (i) applied current, (ii) particle distribution and (iii) compressive strain on the response time of MRE were addressed. The results revealed that the three factors can affect the response characteristic of MRE quite significantly. Besides the intrinsic importance for contributing to the response evaluation and effective design of MRE device, this study may conduce to the optimal design of controller for MRE control system.